Spirit of Steamboat - Johnson, Craig (New York Penguin Books, 2013)
Sheriff Walt Longmire is in his office reading A Christmas Carol when he is interrupted by a ghost of Christmas past : a young woman with a curious scar and more than a few questions about his predecessor, Lucian Connally. Walt's on his own this Christmas Eve, so he agress to help her. At the Durant Home for Assisted Living, Lucian is several tumblers into his Pappy Van Winkle's and swears he's never clapped eyes on the woman before. Disappointed, she whispers a word that take them all back to Christmas Eve 1988 back to a decrepit WWII bomber and a whiskey-soaked piolt, back to a young girl with the slimmest chaqnce of survival, back to Steamboat.
102151
Keywords: Longmire, Walt; Mysteries -- Fiction; Sheriff Stories; Christmas Stories; Mystery Stories